2018
DOI: 10.1002/anie.201810413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Derivatization of 1,1‐[18F]Difluorinated Alkenes

Abstract: Ag eneral method for the synthesis of 1,1-[ 18 F]difluorinated alkenes from [ 18 F]fluoride is reported. This transformation is highly regioselective giving the desired 18 Ffluoroalkenes with radiochemical purities of up to 77 %within 20 minutes and am olar activity (A m )o f1GBq mmol À1 .T he transformations are operationally simple to perform and were readily translated onto acommercial automated synthesis unit. The resultant 1,1-[ 18 F]difluorinated alkene motif is prevalent in numerous drug molecules,a nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…This radiochemistry underwent various improvements (Kramer et al 2020). In 2020, Riss and Scott implemented this protocol for the synthesis [ 18 F]N-methyl lansoprazole ([ 18 F]NML) (4.6% RCY and A m = 120.1 GBq/μmol), a candidate for Alzheimer's Tau imaging (Frost et al 2019). In 2019, Tredwell reported that 1,1-[ 18 F]difluoroalkenes (up to 77% RCY) are accessible upon 18 F-fluorination of fluoroalkenyl(aryl) iodonium triflates with [ 18 F]KF/Kryptofix ® (Fig.…”
Section: Radiosynthesis Of [ 18 F]trifluoromethyl-containing Moleculesmentioning
confidence: 99%
“…This radiochemistry underwent various improvements (Kramer et al 2020). In 2020, Riss and Scott implemented this protocol for the synthesis [ 18 F]N-methyl lansoprazole ([ 18 F]NML) (4.6% RCY and A m = 120.1 GBq/μmol), a candidate for Alzheimer's Tau imaging (Frost et al 2019). In 2019, Tredwell reported that 1,1-[ 18 F]difluoroalkenes (up to 77% RCY) are accessible upon 18 F-fluorination of fluoroalkenyl(aryl) iodonium triflates with [ 18 F]KF/Kryptofix ® (Fig.…”
Section: Radiosynthesis Of [ 18 F]trifluoromethyl-containing Moleculesmentioning
confidence: 99%
“…identity of the aryl group. 5 Of the groups tested 4methoxyphenyl was found to give the desired 1,1-18 Fdifluoroalkene selectively with no formation of 4-[ 18 F]fluoroanisole. Addition of (2,2,6,6-tetramethylpiperodone-1yl)oxidanyl (TEMPO) was found to significantly improve the reaction (Scheme 5a).…”
Section: Scheme 4 Nucleophilic Substitution Of (E)-β-alkyl(alkenyl)iomentioning
confidence: 96%
“…The reduction of the 1,1-18 F-difluorinated alkene was also possible within 5 minutes at room temperature, to yield (4) in 49 ± 4 % (n = 3) RCP. Treatment of (1) with Selectfluor in water/CH3CN gave (5) in 61 ± 4 % (n = 3) RCP. The 1,3-dipolar cycloaddition of (1) with an in-situ generated azomethine, gave the 3,3-[ 18 F]difluoropyrrolidine (6) in 92 ± 3 % (n = 3) RCP.…”
Section: Scheme 4 Nucleophilic Substitution Of (E)-β-alkyl(alkenyl)iomentioning
confidence: 99%
See 1 more Smart Citation
“…This substructure displays unique reactivity relative to typical alkenes; specifically, the distinct electronic character of the termini enables differential functionalization of each carbon atom . Transition-metal-free and transition-metal-catalyzed reactions exploit this reactivity through selective addition of nucleophiles to the difluorinated position over the nonfluorinated position, to generate β-fluoroanionic , or β-fluoroorganometallic intermediates, which readily undergo β-fluoride elimination to generate monofluorinated products (Figure a), even under biological conditions . Though this facile β-fluoride elimination under both basic and transition-metal-catalyzed conditions enables access to monofluoroalkene-based products, the elimination reduces the synthetic utility of gem -difluoroalkenes toward accessing difluorinated products.…”
Section: Introductionmentioning
confidence: 99%